2000
DOI: 10.1002/1520-6858(2000)3:4<169::aid-sys1>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Coping with changes: Causes, findings, and strategies

Abstract: There is no engineering of successful systems without any changes; they are the rule and not the exception in product development. To uncover the problems, rationales and goals associated with changes during the life cycle of a system, an exploratory case study in German industry was conducted. Causes and reasons for changes are described, as well as five strategies to cope with changes and the related methods. One example will show how to successfully prevent and front-load changes. Though the preferred strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
114
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 8 publications
2
114
0
3
Order By: Relevance
“…The failure of what was supposed 50 Influence. 51 Evaluate event, identify strategies, evaluate strategies; decision to reactivate orbiter. 52 Opportunity to exercise payload option.…”
Section: The Reactivation Of Orbiter and The Emergence Of Explorermentioning
confidence: 99%
See 2 more Smart Citations
“…The failure of what was supposed 50 Influence. 51 Evaluate event, identify strategies, evaluate strategies; decision to reactivate orbiter. 52 Opportunity to exercise payload option.…”
Section: The Reactivation Of Orbiter and The Emergence Of Explorermentioning
confidence: 99%
“…[51] identifies eight causes and rationales for change in product development: (1) needs and requirements, (2) feedback and complaints, (3) complexity, (4) degree of innovation, (5) change impacts, (6) communication and coordination, (7) time, and (8) decision discipline. Fricke and Schulz [24] identifies three more drivers of development change: a dynamic marketplace, technological evolution, and variety of environments.…”
Section: Principle Of Change Response and Its Corollarymentioning
confidence: 99%
See 1 more Smart Citation
“…Change initiated in one part of the system tends to have knock-on effects, triggering follow-up changes in other parts. This phenomenon known as change propagation Fricke et al 2000;Clarkson, Simons, and Eckert 2004) is very common to engineering products due to the high interconnectivity between their components. The first change in such a propagation chain is termed initiated change and the rest emergent changes (Eckert, Clarkson, and Zanker 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Fricke et al (2000) concluded from a survey with German companies that 30% of daily work of engineers and managers is related to ECs. Maier and Langer (2011) confirmed this for Danish companies based on a survey with more than 90 engineering firms from different industry sectors and sizes in Denmark.…”
Section: Introductionmentioning
confidence: 99%